2014
DOI: 10.1155/2014/412075
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Expansion of Functional Human UCB-HSCs/HPCs by Coculture with AFT024-hkirreCells

Abstract: Kiaa1867 (human Kirre, hKirre) has a critical role in brain development and/or maintenance of the glomerular slit diaphragm in kidneys. Murine homolog of this gene, mKirre expressed in OP9 and AFT024 cells could support hematopoietic stem cells/hematopoietic progenitor cells (HSC/HPC) expansion in vitro. HKirre is also expressed in human FBMOB-hTERT cell line and fetal liver fibroblast-like cells but its function has remained unclear. In this paper, we cloned a hKirre gene from human fetal liver fibroblast-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…It was known that UCB LTC-IC were present among the CD34 1 /CD38cell fraction and LTC-IC assays exhibit multilineage differentiation ability and major proliferative potential, which was regarded as a functional measure of self-renewal. 39 Our results showed that the frequency of LTC-ICs from 3D-Mix was statistically higher than the other two culture systems, which demonstrated that 3D-Mix contained a higher more primitive hematopoietic cells ex vivo compared with the other training systems and possessed the important ability of fostering a large pool of quiescent HSCs which is a critical niche characteristic in vivo. Difference in the percentage of chimerism of human CD45 1 cells among BM cells of mice transplanted with cultured cells strongly suggested 3D-Mix supported more ex vivo-generated HSCs with ability to sustain and reconstitute long-term human hematopoiesis in vivo, compared with the other training systems.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It was known that UCB LTC-IC were present among the CD34 1 /CD38cell fraction and LTC-IC assays exhibit multilineage differentiation ability and major proliferative potential, which was regarded as a functional measure of self-renewal. 39 Our results showed that the frequency of LTC-ICs from 3D-Mix was statistically higher than the other two culture systems, which demonstrated that 3D-Mix contained a higher more primitive hematopoietic cells ex vivo compared with the other training systems and possessed the important ability of fostering a large pool of quiescent HSCs which is a critical niche characteristic in vivo. Difference in the percentage of chimerism of human CD45 1 cells among BM cells of mice transplanted with cultured cells strongly suggested 3D-Mix supported more ex vivo-generated HSCs with ability to sustain and reconstitute long-term human hematopoiesis in vivo, compared with the other training systems.…”
Section: Discussionmentioning
confidence: 56%
“…PCR analysis of p21 which is an essential regulator for the quiescence of HSC also confirmed flow cytometric results, which showed that p21 of HSCs from 3D‐Mix was significantly higher than that from 3D‐MSCs and 3D‐HUVECs, indicating that the a large percentage of HSCs from 3D‐Mix the was maintained in the G0 stage of the cell cycle. It was known that UCB LTC‐IC were present among the CD34 + /CD38 – cell fraction and LTC‐IC assays exhibit multilineage differentiation ability and major proliferative potential, which was regarded as a functional measure of self‐renewal . Our results showed that the frequency of LTC‐ICs from 3D‐Mix was statistically higher than the other two culture systems, which demonstrated that 3D‐Mix contained a higher more primitive hematopoietic cells ex vivo compared with the other training systems and possessed the important ability of fostering a large pool of quiescent HSCs which is a critical niche characteristic in vivo .…”
Section: Discussionmentioning
confidence: 62%
“…The role of vascularization has already been shown as essential to support organ function and regulation of cell fate choice decisions, organization and differentiation ( Itkin et al, 2016 ). Up until recently, the vascular system has been widely depreciated in the field of BM bioengineering to support HSCs, as can be demonstrated by the small number of studies using endothelial cells (ECs) in co-culture ( Khan et al, 2014 ). This is in spite of the fact that the importance of the vascular system in the BM has been largely demonstrated by in vivo animal studies ( Ohneda et al, 1998 ; Acar et al, 2015 ; Itkin et al, 2016 ; Xu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Irre cell recognition module (IRM; Fischbach et al, ), an evolutionarily conserved, structurally and often functionally related family of proteins belonging to the immunoglobulin superfamily of CAMs offers a good example of CAM functional diversity and versatility: its involvement in cell–cell recognition processes range from axonal guidance in nematodes to glomerular slit diaphragm assembly and maintenance in vertebrates (Neumann‐Haefelin et al, ; Helmstädter et al, ). Also, the requirement of mammalian IRM components for murine and human stem cell survival in vitro has been demonstrated (Ueno et al, ; Khan et al, ). In Drosophila melanogaster , the IRM includes the products of four genes: roughest , ( rst also known as irreC‐rst; Boschert et al, ; Ramos et al, ), the first to be identified and best genetically characterized of the group; its paralogue, kin‐of‐irre ( kirre also known as duf ; Ruiz‐Gomez et al, ; Strünkelnberg et al, ); sticks‐and‐stones ( sns ; Bour et al, ); and hibris ( hbs ; Dworak et al, ).…”
Section: Introductionmentioning
confidence: 99%